Política na web : um estudo sobre o uso de redes e mídias sociais pelos candidatos à prefeitura de Porto Alegre em 2012 - Bianchini, Aline Feijó (2013)
The growing use of internet in politics, since mid 1990s, has brought some important questions about the use of digital communication tools in political on-line campaigns. In this context, the social networks websites have figured as the most important platforms, receiving greater attention from candidates and political parties. These can be used as social medias providing means to propagate and disseminate information or as social networks propitiating exchange and trading environments and the creation of bonds with the civil sphere, offering a space for the expansion of political participation and, consequently, the development of democracy. Through an study with ethnographic inspirations and techniques such as participant observation and in-depth interviews, this research seeks to understand how these tools are being used and to what extent help the approach of the civil and political classes, creating real social networks and paving the way for a more direct conversation between the public and political spheres.